Switching Control Strategy to Minimize Dual Active Bridge Converter Losses - Oggier, German Gustavo (2009)
A switching control strategy to control the power flow and minimize the total power losses of the dual active bridge converter topology is proposed in this paper. The control strategy consists of driving the bridge with the largest DC voltage to generate a three-level pulsewidth-modulated (PWM) voltage waveform. This PWM is ruled by two manipulated variables: the phase shift between the primary and secondary transformer voltages and the modulation index. These variables are calculated using an algorithm that is deduced on the basis of particular calculation and analysis of converter losses, which are also presented in this paper. An experimental prototype was implemented to validate the theoretical analysis and feasibility of the proposal. The experimental results revealed that the overall efficiency of this converter can be improved up to 10% using the control strategy instead of the conventional one.